Money in politics campaign fundraising in the 2020 presidential elections - Myers, Cayce, 1982- (Lexington studies in political communication., 2022)
"Money in Politics explores the political fundraising of the 2020 presidential election from the primaries through the General Election, illustrating the importance of campaign fundraising and examining how campaign contributions are now a political topic in the 2020s"--